The Impact of Social Media on Buying Decision of Pempek Mackerel (Scomberomorus commerson) in Makassar City - Tasmara, A. Fitri; Baso, Aris; Amiluddin, Amiluddin; Kasri, Kasri; Yusuf, Djumran (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2021)
This study aims to determine the characteristics of consumers who decide to buy based on social media advertisements and to find out what factors influence the purchasing decisions of mackerel fish pempek consumers in Makassar City. This research was conducted from January to March 2021. The type of research used was a survey. Research data was collected by interview method and questionnaires were distributed to 94 respondents who had bought mackerel fish pempek products online. The sampling method used is a sampling technique where the research goes directly to the field by taking respondents (samples) from the representative population by using questionnaires as the main data collection. The data sources used are primary data and secondary data and then analyzed using multiple linear regression analysis. The consumers of mackerel fish pempek in Makassar City come from various groups ranging from young people under 19 years old to elderly people over 45 years old, like students, civil servants, to housewives. Based on the results of the research, the variables of product, price, promotion, place, service, and trust together have a positive and significant effect on consumer purchasing decisions with an Fcount value of 20.935 which is greater than the Ftable value of 2.205. Partially, the product variable has a positive and significant effect on purchasing decisions with a tcount value of 2.859 > from a ttable value of 1.9876. The value of Adjusted R Square obtained from the test results of the Coefficient of Determination (R2) on purchasing decisions of 0.591 means that 59.1% of purchasing decisions are influenced by product, price, promotion, place, service, and trust. While the remaining 40.9% is influenced by other factors not included in this study.